Sedimentation and Mitigation Strategies to Maintain Benanga Dam Capacity, North Samarinda - Nur, Alpian; Fadlin, Feri (IJEBD (International Journal of Entrepreneurship and Business Development), 2024)
Benanga Dam, located in Lempake, North Samarinda, East Kalimantan, plays a crucial role in controlling water flow and storage. Initially designed with a capacity of 1.6 million cubic meters, the dam's capacity has significantly reduced to approximately 500,000 cubic meters due to sedimentation over time, exacerbated by human activities such as illegal mining and deforestation in the upstream areas. This sedimentation has not only decreased the dam’s capacity but also increased flood risks in the Karang Mumus River Basin, as evidenced by severe flooding events in recent years. To address this issue, a bathymetric survey using echosounder technology was conducted to assess the current state of the dam’s capacity. The survey results from 2018 and 2022 reveal an increase in reservoir volume by 111,941 cubic meters, attributed to dredging activities in 2021 by the Ministry of Public Works and Housing. However, ongoing sedimentation, estimated at 27,985 cubic meters per year, poses a significant threat to the dam’s capacity. Without effective mitigation strategies, it is projected that the reservoir will reach its normal water level elevation of +7.2 meters within 7 to 8 years. This study underscores the urgent need for regular contour measurements and dredging efforts to maintain the dam’s functionality and mitigate flood risks in the surrounding areas.